Production of cellulosic ethanol in Saccharomyces cerevisiae heterologous expressing Clostridium thermocellum endoglucanase and Saccharomycopsis fibuligera beta-glucosidase genes - Jeon, Eugene; Hyeon, Jeong-eun; Suh, Dong Jin; Suh, Young-Woong; Kim, Seoung Wook; Song, Kwang Ho; Han, Sung Ok (KOREAN SOC MOLECULAR & CELLULAR BIOLOGY, 2009)
Heterologous secretory expression of endoglucanase E (Clostridium thermocellum) and beta-glucosidase 1 (Saccharomycopsis fibuligera) was achieved in Saccharomyces cerevisiae fermentation cultures as an alpha-mating factor signal peptide fusion, based on the native enzyme coding sequence. Ethanol production depends on simultaneous saccharification of cellulose to glucose and fermentation of glucose to ethanol by a recombinant yeast strain as a microbial biocatalyst. Recombinant yeast strain expressing endoglucanase and beta-glucosidase was able to produce ethanol from beta-glucan, CMC and acid swollen cellulose. This indicates that the resultant yeast strain of this study acts efficiently as a whole cell biocatalyst.
Keywords: RECOMBINANT KLEBSIELLA-OXYTOCA; AMORPHOUS CELLULOSE; MICROCRYSTALLINE CELLULOSE; CRYSTALLINE CELLULOSE; YEAST-STRAIN; FERMENTATION; DEGRADATION; HYDROLYSIS; CELLULASES; CELLOBIOSE